System Identification and Control for Scrubber Unit at MLNG - lkhwan, Mohd Farid lzzat (Universiti Teknologi Petronas, 2011)
Nowadays, there are a lot of research that focus on plant improvement; especially in Malaysia Liquefied Natural Gas (MLNG). Without these improvement, the outstanding cost for the plant operation could not be reduced; these improvement is needed to reduce the cost operation so that more revenue will be gained. Thus, optimization are needed to develop profit in any methods available; for this case is to reduce cost of plant operation. Before the project can proceed, research on System Identification and the process are needed. In this paper, the first approach for optimization is to model the plant step test data. Step test data was done in MLNG. Then, obtained data was identified by using System Identification Toolbox in MATLAB. The data was modeled by using the System Identification methods available such as Auto Regression eXogenous (ARX), Box Jenkins (BJ), and also State Space Analysis. The model will be estimate and validate, hence the best model method will be determined by Best Fit Analysis. Then, the model will be control by using poleplacement method and projected output will be compared with the plant data. The outcome of this project proven that the plant can be more optimized with deeper research and analysis of the plant. The more optimized the plant will be, the more profit gain the plant will be.